Crossroads in Christology: A Festschrift for Ellen M. Leonard, C.S. - Anderson, Anne (Toronto journal of theology, 2000)
This festschrift honours Ellen Margaret Leonard for her years of service to the Toronto School of Theology and to the University of St. Michael's College, as she begins this new stage in her career. We are most thankful that she does not intend to abandon these academic institutions, or those of us to whom she has been colleague, mentor, sister or friend, or the larger academic world oftheology and the Christian community. Loyalty and a continued interest in those whose lives she has touched is a highly predictable quality in Ellen.